Implementasi Pemanfaatan AI Sebagai Media Informasi Melalui Pesan Aplikasi Whatsapp - Ahmad Ghumaydi; Tata Sutabri (JURNAL RISET INDRAGIRI, 2024)
The digital era has produced major changes in various dimensions of human life, especially in the fields of communication and information retrieval. This research seeks to design and implement an artificial intelligence (AI)-driven chatbot, integrated with the WhatsApp platform through the utilization of the ChatGPT API. The research methodology used follows the waterfall model, which consists of several phases such as requirements analysis, design, development, implementation, and system testing. The findings of this study show that the developed WhatsApp chatbot is capable of delivering information in a timely, accurate, and real-time manner, as well as offering relevant responses to user queries. The system underwent rigorous testing to evaluate the functionality, responsiveness, and validity of the information provided, yielding favorable results in terms of efficiency and time-saving benefits for users. The implications of this study suggest increased effectiveness in information dissemination, particularly in academic environments and the public service sector. Nonetheless, this study recognizes certain limitations that require further exploration and improvement, including the expansion of service capabilities and the integration of real-time data processing to accommodate a wider range of applications.